2008
DOI: 10.1177/1075547008319435
|View full text |Cite
|
Sign up to set email alerts
|

Using Student-Produced Media to Promote Healthy Eating

Abstract: This study evaluated the effectiveness of an intervention in which fourth and fifth graders participated in an after-school program where they produced a media campaign that focused on increasing fruit and vegetable (FV) consumption. Researchers measured the effectiveness of the media campaign in changing the home nutrition environment (e.g., FV availability and parental support). Quantitative and qualitative measures were also used to evaluate the effect of the intervention on the children's self-efficacy, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Several of studies had multiple publications reporting results (e.g., outcomes reported at different time points): Ammerman et al [18,19,311], Bere [139,312,313]; Bere et al [140,314,315], Byrd-Bredbenner et al [146,316], Ciliska et al [15,317], Chen et al [48,318], Colby [247,319], Covelli [79,320], Cullen et al [253,321], Gortmaker et al [163,322], Haarens et al [166,323], Hendy et al [55,324], Hollar et al [96,325,326], Hopper et al [174,327], Jimenez et al [100,328,329], Latimer [273,330], Lautenschlager and Smith [275,331], Lytle et al [191,332,333], McCormick et al [285,334], Nicklas et al [198,335], Parmer et al [203,336], Reinaerts et al [217,337], Tak et al [121,338,339], Tanner et al [120,340], Taylor et al [229,341], Thomas et al [42,342], Thompson et al [231,232,343], Walker [267,303], Wardle et al [69,344], and Wrigley [306,345]. The number of citations for each study design and the reported outcome measures are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several of studies had multiple publications reporting results (e.g., outcomes reported at different time points): Ammerman et al [18,19,311], Bere [139,312,313]; Bere et al [140,314,315], Byrd-Bredbenner et al [146,316], Ciliska et al [15,317], Chen et al [48,318], Colby [247,319], Covelli [79,320], Cullen et al [253,321], Gortmaker et al [163,322], Haarens et al [166,323], Hendy et al [55,324], Hollar et al [96,325,326], Hopper et al [174,327], Jimenez et al [100,328,329], Latimer [273,330], Lautenschlager and Smith [275,331], Lytle et al [191,332,333], McCormick et al [285,334], Nicklas et al [198,335], Parmer et al [203,336], Reinaerts et al [217,337], Tak et al [121,338,339], Tanner et al [120,340], Taylor et al [229,341], Thomas et al [42,342], Thompson et al [231,232,343], Walker [267,303], Wardle et al [69,344], and Wrigley [306,345]. The number of citations for each study design and the reported outcome measures are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%